Persephone the phony - Holub, Joan (Holub, Joan. Goddess girls., 2010)
Despite the warnings of her friends at Mount Olympus Academy, Persephone befriends bad-boy Hades, but following her mother's advice to "go along to get along" complicates her relationships with all of them.